Journal Enfoque – Reflexão Contábil: an analysis of the publications (Revista Brasileira de Contabilidade e Gestão, 2013)
Scientific works started to transit in the form of letters between the scientists and their associations, which gave birth, in the XVII century, to scientific publications. These publications appear as an opportunity for the scientific community to disseminate knowledge and their new theories. Popularization of scientific journals on accounting in Brazil is quite recent, thus motivating the analysis of publications on this area. The research targets analyzing the scientific articles published on the Journal Enfoque: Reflexão Contábil, outlining the profile of the authors and of the publications. In order to do this, 260 articles were analyzed, which were published from 1990 to 2011 and after that bibliometric methods were applied. The following variants were observed: volume's distribution, articles and authors; distribution of author`s genres; distribution of the author's titles; author`s classification in public and private institution; distribution of the amount of references per article; distribution of the number of pages per article; classification of authors based on their states; distribution of authors per region; foreigner's participation; and, at last, the classification of the macro-themes. It was observed a great number of professors in the total of publications, and a discreet amount of graduates and private universities, being the majority of authors from Paraná.
Keywords: bibliometrics; scientific journals; accounting reflection; Revista Enfoque